Exercise Prescription Improve the Rehabilitation of a Child With Viral Encephalitis Sequelae: A Case Report - Wang, Yang; Kang, Xiaodong; Jiao, Jiao; Zhou, Jihe; Chow, Bik-Chu; Baker, Julien S.; Zhao, Li; Liu, Siyu (Frontiers in Pediatrics, 2022)
This study conducted a personalized exercise prescription intervention on a child with viral encephalitis sequelae (VES). The purpose was to observe the rehabilitation process from the aspects of brain activation, and the curative effects on balance function and gait. A further aim was to explore the possible nerve biomechanical mechanisms between the extent of brain activation and the improvement in balance function and gait. A 12-week exercise prescription was used as the treatment method, and functional near-infrared spectroscopy (fNIRS), balance function test system, plantar pressure distribution system, and 3D gait system were used to assess the effects of the rehabilitation process pre and post the intervention. Following the exercise prescription intervention: 1) fNIRS showed that brain activation in the S1-D1, S1-D2, S1-D3, S2-D1, S3-D2, S3-D3, S4-D3, S5-D5, S5-D6, S5-D7, S7-D6, S7-D7, S8-D7 and S8-D8 increased significantly (P<0.05). 2) The balance test showed that the the area of motion ellipse and movement length of the child with eyes open decreased significantly and area of motion ellipse, back and forth swing, left and right swing and movement length of the child with eyes closed all decreased significantly (P<0.05). 3) The static plantar pressure distribution demonstrated that the pressure center of the left and right foot decreased significantly (P<0.05) from 5.3° dislocation in a straight line in the sagittal plane to 1°; an increment of the pressure loading was found on the forefoot of both feet compared with what was recorded in the pre-test. 4) The testing results of the 3D gait system showed that she had a shortened time of unilateral support phase and prolonged swing phase on the affected leg (P<0.05), compared to that of the non-affected leg. Furthermore, the dual support phase had also been prolonged (P<0.05). Conclusion: 12 weeks’ individualized exercise training can enhance the activation in the motor areas and improve balance function and gait in a child with VES.